Toward standardized brain tumor tissue processing protocols in neuro-oncology: a perspective for gliomas and beyond - Rodriguez, Analiz; Ahluwalia, Manmeet S.; Bettegowda, Chetan; Brem, Henry; Carter, Bob S.; Chang, Susan; Das, Sunit; Eberhart, Charles; Garzon-Muvdi, Tomas; Hadjipanayis, Costas G.; Hawkins, Cynthia; Jacques, Thomas S.; et al. (Frontiers in Oncology, 2024)
Implementation of standardized protocols in neurooncology during the surgical resection of brain tumors is needed to advance the clinical treatment paradigms that use tissue for diagnosis, prognosis, bio-banking, and treatment. Currently recommendations on intraoperative tissue procurement only exist for diffuse gliomas but management of other brain tumor subtypes can also benefit from these protocols. Fresh tissue from surgical resection can now be used for intraoperative diagnostics and functional precision medicine assays. A multidisciplinary neuro-oncology perspective is critical to develop the best avenues for practical standardization. This perspective from the multidisciplinary Oncology Tissue Advisory Board (OTAB) discusses current advances, future directions, and the imperative of adopting standardized protocols for diverse brain tumor entities. There is a growing need for consistent operating room practices to enhance patient care, streamline research efforts, and optimize outcomes.